Exploring the Potential of the Roblox Platform for Developing Islamic Religious Education Learning - Tajussubchi, Ikmal; Amien, Saiful; Kamaludin, Mohammad (At-Tarbiyat, 2024)
This research explores the potential use of Roblox, a Metaverse platform, in the development of Islamic Religious Education (PAI). It addresses the increasing need for innovative and interactive learning tools to effectively teach complex religious concepts such as Aqidah, Ibadah, Mu’amalah, and Islamic history. The study’s main objective is to assess how Roblox can create immersive, interactive learning environments aligned with Bruner’s learning theory and Islamic educational principles, enhancing students' understanding and internalization of Islamic values. Employing a descriptive qualitative approach, the research uses library research methods to collect, validate, and analyze data from various sources on the use of Roblox in education. Key findings reveal that Roblox, with its features for creating simulations, user-generated content, and collaborative interactions, is well-suited for PAI learning. The platform supports Bruner’s three stages of learning—enactive, iconic, and symbolic—allowing students to gain practical, visual, and abstract understanding of religious teachings. The study concludes that Roblox has significant potential as an educational tool, offering a dynamic, holistic, and meaningful learning experience that not only teaches religious concepts but also aids in the internalization of Islamic values, thereby promoting a deeper and more engaging learning process. Integrating Roblox into educational curricula could foster greater understanding and application of Islamic teachings in students' daily lives.